The Six-Party Talks on North Korea Dynamic Interactions among Principal States - Hur, Mi-yeon (Springer Singapore, 2018)
The book traces the past decade of dynamic interactions among the concerned states involved in the Six-Party Talks on North Korean nuclear programs. Unlike existing studies which usually dissect incidents of the talks, the book provides a comprehensive systemic analysis of the Six-Party Talks process from A to Z. These new insights into the nuclear drama in the Northeast Asian region will be of value to scholars, policy makers, and analysts. .